KEMISKINAN PENGRAJIN ROTAN DI DESA LUBUK GAUNG KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Rosmia "; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Lubuk Gaung Village, Siak Kecil District, BengkalisRegency. This study purpose to find out the reason what rattan craftsman are still stay withtheir work as a rattan craftsman, and to know the effort to overcome poverty both from rattancraftsman and from the government. This research was given the title of "Poverty of RattanCraftsman in Lubuk Gaung Village Siak Kecil District Bengkalis Regency". The ideaproblem in research is what rattan craftsman still survive with his work as a rattan craftsmanand how to overcome poverty both from rattan craftsman and from the government. Thepopulation in this research is rattan craftsman in Lubuk Gaung Village, Siak KecilSubdistrict, Bengkalis Regency, the sampling technique in this research is using the censusmethod that is the sample determination technique in the research if all members of thepopulation are used as the sample. In this study the population of respondents is many as 55people, so that all the population used as sample. The data analysis used by the researcher isdescriptive quantitative data analysis. The required data is collected through Observation,Questionnaire (Questionnaire), Documentation. The result of the research shows that thereason what rattan craftsman still survive with their jobs because of economic factors thedemands of life needs expenditure that constant must to complete, Then the factor of jobopportunity, because unable to compete in the world of work, furthermore the factor of workexperience it is difficult for rattan craftsman to try new jobs and the last reason because ofcultural factors that tend to follow the work of parents. The effort made by rattan craftsman inLubuk Gaung Village to overcome poverty is by working together with wives, by doing sidejob such as gardening, being a laborer, selling corn cakes, raising cattle, planting palmseedlings, and following association activities. Efforts by local governments to overcomepoverty include the assistance of houses, cattle, solar power, 3 kg LPG gas, poor rice (raskin),school operational support (bos), public health insurance (Jamkesmas) and the governmentalso provides capital loans through UED-SP Harapan Bersama program.Keywords: Poverty, Rattan Craftsman, Overcoming Poverty